Sensory atributes and physico-chemical characteristics of the coffee beverage from the IAPAR cultivars - Scholz, Maria Brígida dos Santos; de Figueiredo, Vitória Ribeiro Garcia; da Silva, Joyce Vânia Nogueira; Kitzberger, Cíntia Sorane Good (Coffee Science - ISSN 1984-3909, 2013)
The genetic characteristics together with environmental conditions determine the quality of coffee beverage,so the selection of new cultivars of coffee requires information from sensory attributes in different environmental conditions. The aim of the present study was to evaluate the physico-chemical and sensory characteristics of the coffee cultivars IPR 97, IPR 98, IPR 99, IPR 100 , IPR 101, IPR 102, IPR 103, IPR 104, IPR 105, IPR 106, IPR 107, IPR 108 and IAPAR 59,Bourbon, Icatu and Tupi grown in the municipalities of Paranavaí and Itaguajé - PR, season 2007-2008. We evaluated the characteristics of the roasting of the beans and beverage. The sensory attributes were evaluated by descriptive sensory analysis of Free Choice Profilling. Significant correlations were observed between the different characteristics of the roasted bean and the beverage. In the Principal Component Analysis (PCA), the variables of roasted bean and beverage grouped the coffees, observing that most cultivars from Itaguajé showed darker coffees with higher acidity and density of roasted bean when compared to Paranavaí. The attributes of color appearance and brightness of coffee, coffee aroma, green aroma, sourand bitter taste, green flavor and body texture were the main attributes responsible for the separation between sites. Bean color and acidity of the beverage were physico-chemical and sensory characteristics important for discriminating coffeecultivars and production sites. This information serves to aid in the deployment of new crops enhancing desirable sensory attributes of each cultivar.